Pemanfaatan Spent Bleaching Earth (SBE) Dan Tandan Kosong Sawit (TKS) Sebagai Bahan Baku Pembuatan Briket - Niko Ronaldo P. S; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia's dependence on fossil energy has made the availability of petroleum decrease drastically. This situation was driven by increased growth in the industrial sector and population. The depletion of fossil energy reserves must be immediately balanced with the provision of alternative energy, one of the uses of biomass as an alternative fuel to replace fossil fuels is to make it into briquettes. Biomass waste produced from the palm oil industry are solid waste of empty palm oil fruit bunches and solid waste of spent bleaching earth. The hoped that empty palm oil fruit bunches waste and spent bleaching earth solid waste can be reused so that waste does not become an environmental problem because it is existence has not been optimally untilized. Keywords: Briquettes, Spent Bleaching Earth, Empty Palm Oil Fruit Bunches